2017
DOI: 10.1002/pssb.201700276
|View full text |Cite
|
Sign up to set email alerts
|

Structure and elastic properties of black phosphorus nanotubes: A first-principles study

Abstract: We investigate the size dependence of geometric structure and elastic properties of phosphorene nanotubes (PNTs) with armchair and zigzag forms, by using ab initio periodic quantum chemical method combining with the linear combination of atomic orbitals. Nanotubes are constructed by rolling up the non‐planar honeycomb (010) two‐dimensional conventional monolayer. To explain the strength of bonding between P atoms, the bending stiffness and the amount of charge transfer have been calculated. We obtained differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Then both of them will approach the value obtained for the blue P sheets when the tube radius larger than 13 Å. Similar to the blue PNTs, the effect of tube stiffing with increasing radius is also found in black PNTs, AlN nanotubes and ZnO nanotubes with small radius 24,39,40 .
Figure 5The dependence of Young’s modulus for PNTs on radius.
…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Then both of them will approach the value obtained for the blue P sheets when the tube radius larger than 13 Å. Similar to the blue PNTs, the effect of tube stiffing with increasing radius is also found in black PNTs, AlN nanotubes and ZnO nanotubes with small radius 24,39,40 .
Figure 5The dependence of Young’s modulus for PNTs on radius.
…”
Section: Resultssupporting
confidence: 56%
“…7. Interestingly, the band gap of blue PNTs are larger than black PNTs with the same radius 24 . When the radius is small, the band gap of zigzag blue PNTs rise sharply with the increase of radius.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…the luminescence properties of SrBi 2 nb 2 o 9 materials doped with rare-earth ions have not been widely studied. Under 451 nm light excitation, Ho-doped SrBi 2 nb 2 o 9 exhibited a strong green emission centered at 545 nm due to the intra f-f transition from the excited to the ground state of Ho 3+ ions and the concentration quenching effect was observed when reaching 0.4 mol% [3]. in Sr 0.7 er x bi 2.2-x nb 2 o 9 (x = 0.0,0.4,0.6,0.8,1) opto-electro materials, er 3+ ions showed four intense emission bands peaking around 424 (violet), 444 (violet), 464 (Blue), 478 (Blue) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The electronic structure, optical properties, thermal properties, and stability of black phosphorous nanotubes and blue phosphorous nanotubes have been investigated recently. [28][29][30][31][32][33][34][35][36][37][38][39][40] Cao et al studied the lithium-ion storage performance of single-walled black phosphorene nanotubes (SWBPNTs), and demonstrated that black phosphorous nanotubes can be used as a potential anode material for LIB. [30] Additionally, we have studied the characteristics of lithium atoms on zigzag SWBPNTs and found that lithium atoms are easier to adsorb and diffuse inside blue phosphorous nanotubes.…”
mentioning
confidence: 99%